Towards a Devolved Model of Management of OER? The Case of the Irish Higher Education Sector - Risquez, Angelica; McAvinia, Claire; Desmond, Yvonne; Bruen, Catherine; Ryan, Deirdre; Coughlan, Ann (International Review of Research in Open and Distributed Learning, 2020)
This paper reports on the research findings from a national project examining the issues in creating, sharing, using, and reusing open educational resources (OER) in the context of the development of open education in Ireland. One important aspect of the research was to investigate the potential for using existing institutional research repository infrastructure for the purpose of ingesting, managing, and discovering OER produced by academics. This approach would imply a move from previous strategy around a centralised repository at the national level to a devolved model that relies on institutional research repositories. The opportunities and potential barriers to the adoption of this approach were explored through an online survey and focus groups with academics from a range of higher education institutions (HEIs). Also, a focus group of institutional repository managers was convened to discuss the potential of the institutional repositories with those leading their development. Analysis of the data indicates that the devolved approach to institutions would be possible if the right supports and protocols were put in place. It was acknowledged that research repositories could potentially also serve as repositories of teaching materials, fostering parity of esteem between teaching and research. However, a range of important challenges were present, and alternative solutions emerged, which are discussed in the context of the present and future of online OER repositories.